Constrictive Pericarditis After a Stab Wound of the Chest - Carmen Del Giudice; Renato Cosimo; Marco Malvezzi Caracciolo D'Aquino; Enrica Pezzullo; Rossana Bussani; Laura Massa; Marco Pozzan; Renata Korcova; Danilo Ruggiero; Enzo Mazzaro; Gianfranco Sinagra; Paolo Golino; et al. (Annals of Internal Medicine: Clinical Cases)
Constrictive pericarditis is an uncommon cause of diastolic heart failure resulting by impaired cardiac filling from an inelastic pericardium. We present a case of constrictive pericarditis in a 39-years-old man following thoracic penetrating trauma in which histologic specimens have shown pericardial layer invasion by squamous cells from the skin. Moreover, the multimodality imaging approach has been essential for diagnosis and case management.